Economic Factors Influencing the Rate of Inflation in Lao PDR - YOTHSOMFEUANG, Sengsomphabout; SIPHANTHONG, Bounthavy; XIONGTOUA , Tongvang; POUNNALY, Phaivanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Inflation is one of the most pressing challenges in macroeconomic development, especially in Lao PDR. Nowadays, inflation is very important as it is a key indicator of economic planning and studying various factors. In 1998, Laos PDR was affected by the financial crisis in Asia, resulting in inflation rising to 87% and increasing to 134% in 1999. Therefore, the government needs to use monetary and fiscal policies to boost the economy. To study of Economic factors determining the rate of inflation in Lao PDR, the quantitative analysis was used in time series data between 1990-2018 by using Granger Causality variables and values tests using the least squares method (OLS) The result shown that the inflation rate does not affect to the exchange rate (USD currency), however the exchange rate does not affect the inflation rate. The government expenditure does affect money supply, but the money supply does not affect to the government expenditure. GDP does directly affect the money supply, but the money supply does not affect to GDP. Loan’s interest rates does effect to the exchange rate, but the exchange rate does not affect to the Loan’s interest rates with statistical significance at the level of 0.05 Economic factors determining the rate of inflation in Lao PDR, including changes in gross domestic product (GDP) that have similar changes, changes in interest rates, favorable customer loans in the same manner But contrary to the hypothesis and the exchange rate (Kip to USD) is inversely proportional and in contrast to statistical significance of 0.01, while the change in the money supply and the government expenditure do not determine to the inflation rate in Lao PDR.